The Key Role of Personality Functioning in Understanding the Link Between Adverse Childhood Experiences and Loneliness: A Cross-Sectional Mediation Analysis - Jeff Maerz; Roberto Viviani; Karin Labek (Brain Sciences, 2025)
Background and Aims: Loneliness represents a critical public health concern, significantly affecting mental and physical health. Adverse childhood experiences (ACEs) have been recognized as predictors of loneliness, yet the underlying mechanisms remain unclear. The level of personality functioning, determined by self- and interpersonal impairments, has been proposed as a potential mediator but has not been empirically explored in this context. This study examined whether personality functioning mediates the relationship between cumulative and specific types of ACEs and loneliness using a cross-sectional design. Methods: An online survey of 334 participants (mean age = 25.96; 65% female) were assessed for ACEs using a modified version of the KERF-40-I scale, their personality functioning using the Level of Personality Functioning Scale (LPFS-BF), and loneliness using the revised UCLA Loneliness Scale. Results: Higher ACE exposure was significantly associated with loneliness and greater impairments in overall personality functioning and self-functioning. After controlling for other ACE subtypes, emotional neglect remained associated with the overall level of personality functioning, while emotional neglect and sexual violence were associated with self-functioning impairments. Mediation analyses indicated that the overall level of personality functioning was consistent with a full mediation model of the ACE–loneliness association, accounting for 64% of the total effect. When examining self-functioning separately, an indirect effect accounted for 78% of the total association. In models testing specific ACE types, self-functioning fully mediated the associations between emotional neglect, sexual violence, and loneliness. Conclusions: The findings highlight self-functioning impairments as a key mechanism linking both cumulative and specific ACEs and loneliness, suggesting a need for a targeted focus on self-related impairments. Longitudinal studies are needed to clarify the developmental trajectories.